Efeitos cardiovasculares do citral, monoterpeno majoritário do óleo essencial de Cymbopogon citratus, em ratos - Moreira, Flávia Viana (2013)
The monoterpene citral is the major constituent of the essential oil of Cymbopogon citratus, medicinal plant popularly known as capim-limão or capim-santo , widely used to treat hypertension. This study evaluated the cardiovascular effects induced by the citral in normotensive rats by using in vivo and in vitro approaches. In non-anaesthetized rats, citral (1, 5, 10, and 20 mg/kg, i.v.) induced transient hypotension and bradycardia. Both effects were significantly attenuated by the pre-treatment with atropine (2 mg/kg, i.v.), hexamethonium (20 mg/kg, i.v.), sodium thiopental (45 mg/kg; i.p.) or indomethacin (5 mg/kg, i.v.) after dose of 5 mg/kg of the citral. After pre-treatment with L-NAME (20 mg/kg, i.v.), hypotension was significantly attenuated, while bradycardia was not altered. Furthermore, electrocardiogram records demonstrated that citral (10 and 20 mg/kg) was also able to induce sinoatrial block, which was reverted by atropine (2 mg/kg). In rings of rat mesenteric artery pre-contracted with phenylephrine (10 μM), citral (10-5 - 10-2 M) was able to induce relaxations (pD2 = 2.52 ± 0.10; Emax = 103.4 ± 10.2%) that was not affected after removal of the endothelium (pD2 = 2.34 ± 0.15; Emax = 107.2 ± 4.3%) or in rings without endothelium pre-contacted with KCl 80 mM (pD2 = 2.04 ± 0.12; Emax = 101.3 ± 7.1%) or in rings without endothelium after tetraethylammonium (pD2 = 3.25 ± 0.05; Emax = 109.3 ± 9.8%). At concentrations of 3 x 10-4 and 10-3 M, citral was able significantly to inhibit the contractions induced by CaCl2 (from 10- 5 to 10-2 M) or sodium orthovanadate (from 3 x 10-4 to 3 x 10-2 M) up to 88.6 ± 3.1% and 93.3 ± 3.8%, respectively. These results demonstrate that citral induces hypotension, which appears to be caused by activation of muscarinic receptors, NO release and, in part, by PGI2 release, associated to bradycardia, which seems to be due to an activation of muscarinic and nicotinic receptors, involving compounds of central nervous system, and sinoatrial block. Furthermore, citral induces vasorelaxation of mesenteric artery possibly caused by the inhibition of the Ca2+ influx through voltage-operated Ca2+ channels associated to a decrease of calcium sensitivity.